Construct validity of the instrument of digital skill literacy - Muhammad Harlanu; Agus Suryanto; Syahrul Ramadhan; Endang Wuryandini (LPMPP Universitas Negeri Yogyakarta, 2023)
This research is descriptive research that is conducted by quantitative approach to find out the validity and reliability of an instrument. The population in this research is all active college students at the State University of Semarang in nine faculties, taking sample is conducted by probability-sampling that means all population has the same chance to be a research subject. The number of samples in this research is 300 of people. The technique of data analysis on the validity verification in this research used Confirmatory Factor Analysis (CFA) technique. Meanwhile, for the estimation of reliability, the researcher used the formula of Cronbach’s Alpha. The data analysis is supported by JAMOVI program. The result of research shows that a) the instrument of digital skill literacy has fulfilled the criteria of goodness of fit with the result; 1) x2 = 162 dan df = 143; 2) p-value = 0,133; 3) RMSEA 0,021; 4) SRMR = 0,026; 5) and CFI = 0,99; b) the result of CFA shows 20 items that is divided by the indicator such as functional skill beyond, creativity, collaboration, communication, the ability to find select information, critical thinking and evaluation, cultural and social understanding, E-Safety have fulfilled valid criteria with the average score of loading factor is 0.80. c) the reliability of literacy digital skill instrument shows the estimation value which is 0.943 or very reliable.